RĂSPUNDEREA PENALĂ A JUDECĂTORULUI PENTRU INFRACȚIUNI DE CORUPȚIE. luArea DE MITĂ - Costachi, Gheorghe, Cozma Daniela (SUPREMANCE OF LAW, 2018)
The article includes a study on the issue of criminal liability of judges for corruption offenses under Romanian law. After a brief introduction on the phenomenon of corruption, its appearance and its evolution in the Romanian space, the authors emphasize the bribe taking as a relevant offense in the system of corruption offenses. They analyze the composition of the crime based on the legislation in force and the doctrine in the field.